Development of transdermal drug-delivery films with castor-oil-based polyurethanes - Shelke, Namdev B.; Sairam, Malladi; Halligudi, Shivaraj B.; Aminabhavi, Tejraj M. (Journal of Applied Polymer Science, 2007)
Two different types of polyurethanes (PUs) were prepared with castor oil, ethylene glycol, isophorene diisocyanate and castor oil, and isophoren diisocyanate and poly(ethylene glycol) (400 or 600). PU films were prepared and characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, and gel permeation chromatography. We prepared transdermal patches by loading different amounts of drug, plasticizer, and penetration enhancer. In vitro drug permeability through the castor-oil-based aliphatic PU patches was examined with a Keshary-Chien diffusion cell. The effect of castor oil on the film-forming properties and the effect of penetration enhancers on diffusion characteristics of indomethacin (IDM) drug through the castor-oil-based PU were investigated. Prolonged release of IDM was observed from the prepared PU patches. In vitro drug diffusion revealed that slow and prolonged release of IDM was achieved in the absence of penetration enhancers. The use of penetration enhancers showed a significant effect on drug diffusion. (c) 2006 Wiley Periodicals, Inc.
Keywords: castor oil; drug delivery; polyurethane; transdermal